The right to life: Global evidence on the role of security officers and the police in modulating the effect of insecurity on homicide - Simplice Asongu; Jacinta C. Nwachukwu; Chris Pyke (African Governance and Development Institute (AGDI), 2018)
The study investigates the role of security officers and the police in dampening the effect of insecurity on homicides. Insecurity dynamics are measured in terms of access to weapons, violent crime, perception of criminality and political instability. The geographical and temporal scopes are respectively 163 countries and 2010-2015. The empirical evidence is based on Negative Binomial regressions. Three main findings are established. First , security officers and the police significantly lessen the effect of political instability and perception of criminality on homicides. Second , an extended analysis with thresholds suggest that a maximum deployment of security officers and the police is required in order to completely cancel out the impact of both insecurity dynamics on homicides. The concept of threshold represents the critical mass at which the negative conditional effect from the interaction between security officers and the police completely dampens the effect of insecurity dynamics on homicides. Third , the use of security officers and the police is a necessary but not a sufficient condition for the complete eradication of insecurity-related homicides. Policy implications are discussed.
Keywords: K42; P50; 330; Homicides; Global evidence; security